Health-seeking behaviour of human brucellosis cases in rural Tanzania - MacMillan Alastair; Shirima Gabriel; French Nigel P; Kazwala Rudovic; Fitzpatrick Julie; Kunda John; Kambarage Dominic; Bronsvoort Mark; Cleaveland Sarah (BMC, 2007)
Abstract Background Brucellosis is known to cause debilitating conditions if not promptly treated. In some rural areas of Tanzania however, practitioners give evidence of seeing brucellosis cases with symptoms of long duration. The purpose of this study was to establish health-seeking behaviour of human brucellosis cases in rural Tanzania and explore the most feasible ways to improve it. Methods This was designed as a longitudinal study. Socio-demographic, clinical and laboratory data were collected from patients who reported to selected hospitals in rural northern Tanzania between June 2002 and April 2003. All patients with conditions suspicious of brucellosis on the basis of preliminary clinical examination and history were enrolled into the study as brucellosis suspects. Blood samples were taken and tested for brucellosis using the Rose-Bengal Plate Test (RBPT) and other agglutination tests available at the health facilities and the competitive ELISA (c-ELISA) test at the Veterinary Laboratory Agencies (VLA) in the UK. All suspects who tested positive with the c-ELISA test were regarded as brucellosis cases. A follow-up of 49 cases was made to collect data on health-seeking behaviour of human brucellosis cases. Results The majority of cases 87.7% gave a history of going to hospital as the first point of care, 10.2% purchased drugs from a nearby drug shop before going to hospital and 2% went to a local traditional healer first. Brucellosis cases delayed going to hospital with a median delay time of 90 days, and with 20% of the cases presenting to hospitals more than a year after the onset of symptoms. Distance to the hospital, keeping animals and knowledge of brucellosis were significantly associated with patient delay to present to hospital. Conclusion More efforts need to be put on improving the accessibility of health facilities to the rural poor people who succumb to most of the diseases including zoonoses. Health education on brucellosis in Tanzania should also stress the importance of early presentation to hospitals for prompt treatment.